1991
DOI: 10.3109/00207459108985437
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of pineal calcification and melatonin secretion to the pathophysiology of tardive dyskinesia and tourette's syndrome

Abstract: Despite current intensive research, the pathophysiology of tardive dyskinesia (TD), a serious neurological side effect of neuroleptic treatment, is poorly understood. Prompted by the observation of an increased incidence and severity of abnormal perioral movements in neuroleptic-treated pinealectomized, as compared to intact rats, we suggested that the pineal gland exerts a protective effect which mitigates against the development of TD and, by inference, that reduced melatonin secretion may be related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 155 publications
(123 reference statements)
0
13
0
1
Order By: Relevance
“…In addition, both clinical and preclinical evidence provide further support to the notion that melatonin deficiency may be related to the pathophysiology of tardive dyskinesia. Indeed, while nocturnal plasma melatonin levels have been reported to be reduced in neuroleptic-treated schizophrenic patients (Ferrier et al 1982), a significant association between pineal calcification and the presence of tardive dyskinesia was found (Sandyk and Kay 1991). Furthermore, reduction in melatonin secretion has been suggested to be related to tardive dyskinesia associated with depression in bipolar patients (Sandyk 1990).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, both clinical and preclinical evidence provide further support to the notion that melatonin deficiency may be related to the pathophysiology of tardive dyskinesia. Indeed, while nocturnal plasma melatonin levels have been reported to be reduced in neuroleptic-treated schizophrenic patients (Ferrier et al 1982), a significant association between pineal calcification and the presence of tardive dyskinesia was found (Sandyk and Kay 1991). Furthermore, reduction in melatonin secretion has been suggested to be related to tardive dyskinesia associated with depression in bipolar patients (Sandyk 1990).…”
Section: Discussionmentioning
confidence: 94%
“…Melatonin has a lengthy history of beneficial actions. For example, almost two decades ago it was reported as a protector against glucocorticoid damage [74, 75], against some degenerative neurological conditions [76], as an anticancer agent [31, 77–79], and also as an enhancer of immune function [32, 79]. Subsequently, the multiple antioxidant properties of melatonin were described [33, 34, 80, 81] and research on its protective effects against oxidative processes have now been identified under a very wide range of conditions in both experimental animals [82–84] and humans [85, 86].…”
Section: Regulation Under Elevated Oxidative Stress Conditionsmentioning
confidence: 99%
“…Large amounts of evidence, however, also suggest that the pineal calcification was indeed associated with human pathological disorders and aging. Decades ago several studies pointed out the relationship between the pineal calcification and schizophrenia [ 73 , 166 , 167 , 168 ]. The highest pineal calcium content was detected in the pineal gland of patients who died of renal disease associated with hypertension among other diseases [ 169 ].…”
Section: Pineal Gland Calcification (Pgc) Melatonin Production Nmentioning
confidence: 99%